Father–Child Longitudinal Relationship: Parental Monitoring and Internet Gaming Disorder in Chinese Adolescents - Su, Binyuan; Yu, Chengfu; Zhang, Wei; Su, Qin; Zhu, Jianjun; Jiang, Yanping (Frontiers in Psychology, 2018)
Although empirical studies have indicated that parents have an important role in preventing Internet gaming disorder in adolescents, longitudinal research on the parental predictors of Internet gaming disorder is lacking. We used a three-wave cross-lagged panel model to explore the reciprocal association between parental monitoring and Internet gaming disorder, and examined the different impacts of mother– and father–child relationships on this association. A sample of 1490 adolescents aged 10–15 years (M = 12.03, SD = 1.59; 45.4% female) completed assessments at all three points. The cross-lagged model revealed that (a) parental monitoring at T1 predicted lower Internet gaming disorder at T2, and greater Internet gaming disorder at T2 predicted lower parental monitoring at T3; (b) father–child relationship had a reciprocal, indirect effect on the relationship between parental monitoring and Internet gaming disorder, while mother–child relationship did not. These findings suggest that the parental effects (e.g., higher parental monitoring and better father–child relationship) might play a vital role in preventing Internet gaming disorder in adolescents.